Business use of the World-Wide Web - C. Cockburn; T.D. Wilson (Information Research: An International Electronic Journal)
Two methods were employed in this study of the use of the World Wide Web by business: first, a sample of 300 businesses with Web sites, across a wide range of industry types, was examined, by selecting (rather than sampling) companies from the Yahoo! directory. The sites were investigated in relation to several areas - the purpose of the Web site, the use being made of electronic mail and the extent to which multi-media was being utilised. In addition, any other aspects of the site which were designed to make it more interesting to potential customers were also noted. Secondly, an electronic-mail questionnaire was sent to 222 of the 300 companies surveyed: that is, those that provided an e-mail address for contact. 14 were returned immediately due to unknown addresses or technical problems. Of the remaining 208, 102 replies were received, five of which were of no relevance, leaving 97 completed questionnaires to examine; a response rate of 47%, which is surprisingly good for a survey of this kind.